Correlated band structure of electron-doped cuprate materials: Strong Correlations - Dahnken, C.; Potthoff, M.; Arrigoni, E.; Hanke, W. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2006)
We present a numerical study of the doping dependence of the spectral function of the n-typecuprates. Using a variational cluster-perturbation theory approach based upon the self-energyfunctionaltheory, the spectral function of the electron-doped two-dimensional Hubbard model is calculated. The model includes the next-nearest neighbor electronic hopping amplitude t' and a fixed on-site interaction U = 8t at half-filling and doping levels ranging from x= 0.077 to x = 0.20. Our results support the fact that a comprehensive description of the single-particle spectrum of electron-doped cuprates requires a proper treatment of strong electronic correlations. In contrast to previous weak-coupling approaches, we obtain a consistent description of the ARPES experiments without the need to (artificially) introduce a doping-dependent on-site interaction U.